Neural mechanisms of contextual modulation in the retinal direction selective circuit - Xiaolin Huang (Nature Portfolio, 2019)
The mechanisms of contextual modulation in direction selective ganglion cells in the retina remain unclear. Here, the authors find that that On-Off direction-selective ganglion cells are differentially sensitive to discontinuities of dark and bright moving edges in the visual environment and, using synapse-specific genetic manipulations with functional measurements, reveal the microcircuits underlying this contextual sensitivity.